Hubungan Antara Status Sosial Ekonomi Masyarakat dengan Sanitasi di Desa Ampekale Kecamatan Bontoa Kabupaten Maros - Padati, Eunike Christy; Daud, Firdaus; Arifin, Arifah Novia (Biology Teaching and Learning, 2021)
Abstract.Â One of the basic needs for every human being is health. The environment is one of important factor that greatly influences human health, because the environment is a place where humans do all their activities. Every effort made by humans to avoid dangerous waste materials with the aim of improving the quality of the environment is called sanitation. The purpose of this study was to determ ine the relationship between the socio-economic conditions of the community and sanitation. The research design used in this study was a correlational research design using the Spearman Rank analysis technique for variables of education level and income level, while the analysis of the relationship between types of work and sanitation was analyzed using Cramer's contingency coefficient analysis technique. Samples taken were randomly selected by using cluster random sampling technique with a total sample of 120 samples. The results showed that as many as 97 (80%) of respondents had a low level of education ie graduating from elementary school.Â In the sub-variable type of work, the type of work most frequently done was fishermen with 41 respondents with a percentage of 34.16%. In the income level sub-variable, the highest percentage was 58 (48.3%) of respondents in the low income category. Based on the results of the correlation test between the socioeconomic level sub variables with sanitation, the results obtained are there is a relationship between the level of education with sanitation with a syg value of 0.010, there is a relationship between the type of work with sanitation with a syg value of 0.007, and there is a relationship between the level of income with sanitation with syg value of 0.005.Keywords: Education level, type of job, income level, sanitation.